Development and Validation of the Quantification Method for Hydroxychloroquine in Volumetric Absorptive Microsampling (VAMS) Using High-Performance Liquid Chromatography-Photodiode Array - Yahdiana Harahap; Siti Ardyanti Rohadatul 'Aisy; Baitha Palanggatan Maggadani (Hindawi Limited, 2021)
Hydroxychloroquine is an antimalarial drug used for systemic lupus erythematosus, rheumatoid arthritis, and malaria treatment. However, hydroxychloroquine has several side effects such as ocular toxicity, neurotoxicity, gastrointestinal disorder, and also severe toxicity such as cardiotoxicity. Therefore, therapeutic drug monitoring of high dose or long-term use of hydroxychloroquine is needed. This study aims to obtain an optimum and validated analysis and preparation method for hydroxychloroquine in volumetric absorptive microsampling (VAMS) using the high-performance liquid chromatography-photodiode array detector based on the Food and Drug Administration guidelines (2018). Hydroxychloroquine quantification was performed using HPLC-PDA with Waters Sunfire™ C18 (5 µm; 250 × 4,6 mm) column. Mobile phase consists of acetonitrile-diethylamine 1% (65 : 35, v/v) (isocratic elution) and delivered at a flow rate of 0.8 mL/min throughout the 12 minutes run. Sample in VAMS is extracted by liquid-liquid extraction with ammonia 1% and n-hexane-ethyl acetate (50 : 50 v/v) as a extraction solvent. This method has successfully qualified the Food and Drug Administration (2018) parameters, with 2 ng/mL of LLOQ, range of calibration curve 2-6500 ng/mL, and coefficient of correlation 0.9993-0.9997.